Implementation Of Solar Cell Based Smart Chair As A Green Open Space Electric Energy Source - Kango, Riklan; Hadiyanto, Hadiyanto; Pongtularan, Ezra Hartarto; Abas, Mohamad Ilyas (International Journal Papier Advance and Scientific Review, 2021)
This research aims to propose new solutions for alternative sources of electrical energy in open spaces. We validated this solution by implementing a solar cell in a park bench object. Furthermore, analyzing the statistical data by taking the average value of; current, voltage, and power generated by the smart bench object. The experimental results show that the proposed solution has the same performance as conventional lighting. Electric park benches can operate longer using a solar cell with an output power of 26.76 Watt-peak hours. With the large potential of solar power, solar cells' application in an open environment is very suitable. With this electric bench, it is still energy efficient and green energy